Siwa Nata Raja: A Monumental Work From Aesthetic and Heritage Perspectives - Kandiraras, Tudhy Putri Apyutea; Saptono, Saptono; Santosa, Hendra; Sasrani Widyastuti, Ida Ayu Gede (Universitas Negeri Semarang, 2025)
Dance arts related to the great dance are the most popular. This beautiful dance is performed in all regions now. Even in the educational environment, which is the epicenter or center of trends, there is a proliferation of essential dances. One of the dances that marked the beginning of the creation of great dance was the Shiva Nata Raja dance at Institut Seni Indonesia, Denpasar. The Shiva Nata Raja dance still exists today and is a form of transmission or inheritance that is still running well. The question that generally arises in dance development is how to teach it. Ideally, the transition process does not reduce the foremost essence of the dance. A person's understanding of the intricacies of dance can be obscured by the assumption that dance is simple. Therefore, another way is needed so that the main parts of the dance are not lost. Every part of the movement is crucial to learn. The method used to conduct this research is a qualitative descriptive analysis method, which reveals the aesthetics and inheritance of the Shiva Nata Raja dance style. This inheritance process has been going on for approximately 34 years, so the Shiva Nata Raja dance still survives today and can be classified as a monumental dance.